Prospects for Applying Xenon Curative Properties in Pediatrics - Tatiana S. Sabinina; Vladimir G. Bagaev; Ilia F. Alekseev (Педиатрическая фармакология)
The review discusses experimental and clinical trials on applying noble gas Xenon to treat therapeutic conditions in adults, as well as the prospects for its applying in children. Xenon therapeutic effects on the body are based on the healing properties of a noble gas. Xenon is close to the ‘ideal anesthetic’ by its anesthetic properties; but in addition, it possesses organoand neuroprotective as well as anti-stress properties which have been proved in experiment and clinically. Xenon in pediatric practice is an attractive agent because it is non-toxic, effective for the treatment of posthypoxic and traumatic impairments of the central nervous system, pain syndromes and stress conditions at its therapeutic concentration up to 30%.